DAMPAK PENERAPAN PRINSIP NATIONAL TREATMENT TERHADAP IKLIM INVESTASI DI INDONESIA PASCA UNDANG-UNDANG NOMOR 25 TAHUN 2007 TENTANG PENANAMAN MODAL - Abdul Halim Barkatullah (Al-Adl : Jurnal Hukum, 2017)
Investment is the driving force of a country's economy. The state's obligation to regulate investment is due to the complexity of the nature of investment and has an impact on many aspects, ranging from land, labor, capital, taxation and other aspects. The principle of "national treatment" as the basic principle of TRIMs/GATT has been adopted in UUPM. Against this principle in its application should also pay attention to the welfare of the people, where the State's right in making an investment rule for the greatest purpose of people's prosperity and do not turn off investors coming from within the country itself. Impact in the application of the principle of "national treatment" in the Capital Market Law provides fresh angina for the Inventor from abroad. However, in competition between the recipient country of Investment, in the case of licensing of UUPM regulates the licensing mechanism, so before the investor does business, he / she is obliged to obtain the permit. The permit is obtained through one-door integrated services. The one-stop integrated service aims at assisting investors in obtaining ease of services, fiscal facilities, and information on investments, conducted by authorized institutions or agencies.